STUDI MODAL SOSIAL PADA AGROWISATA PETIK SAYUR DI DESA KARANG JAYA KECAMATAN SELUPU REJANG KABUPATEN NREJANG LEBONG - Juliansyah, Rizki; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2023)
ABSTRACTThis study aims to find out who and what is the role of each stakeholder in the management of vegetable picking agro-tourism in Karang Jaya Village, Selupu Rejang District, Rejang Lebong Regency and to find out how social capital is in the management of vegetable picking agro-tourism in Karang Jaya village, Selupu Rejang district, Rejang Lebong district. This research was carried out in Karang Jaya Village, Selupu Rejang District, Rejang Lebong Regency from May to July 2022. The research method used was a survey method, for the sampling method used the Snowball Sampling and Purposive Sampling methods. The data collection methods used in this study were observation and in-depth interviews and documentation. The data processing method used was editing, coding and tabulating and the data analysis used was Likert Scale. The results showed that the stakeholders involved in the management of vegetable picking agro-tourism in Karang Jaya Village were farmers, village government, Village-Owned Enterprises, Tourism Awareness Group and View Garden. The role of each stakeholder in the management of vegetable picking agro-tourism in Karang Jaya Village is a farmer whose role is onfarm activities, participation in planning and development as well as a guide. The village government whose role is the implementation of government administration, development, development, community empowerment, disaster management and assistance in promotion. Then the Village-Owned Enterprises whose role is to support village government programs and capital. Furthermore, the Tourism Awareness Group's role is to coordinate activities, guides/guides and build visitor self-sufficiency. Meanwhile, View Garden's role is to increase the attractiveness and provide facilities for its place. For social capital in the management of vegetable picking agro-tourism, the social capital index is worth 89.33% with the criteria of